Chronic osteomyelitis on an old compound fracture - Shrestha, A; Sah, S Kumar (Journal of College of Medical Sciences-Nepal, 2012)
Osteomyelitis is a common complication of compound fracture of long bones which is difficult to treat. We present a similar case of chronic osteomyelitis on an old malunited compound fracture of distal third left femur in a nine years old child. Management of such cases requires surgery with immobilization, long term appropriate antibiotics and intensive follow up. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 54-57 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6840